Walidacja skali Affective Neuroscience Personality Scales u osób zdrowych - Amiri, Sohrab; Azad-Marzabadi, Esfandiar (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2017)
Aim of the study : To evaluate the psychometric properties of Affective Neuroscience Personality Scales (ANPS). Material and methods : For this purpose, 326 normal participants were selected, then the Affective Neuroscience Personality Scales: Negative and Positive Affect Scale (NAPAS) and the Emotion Awareness Questionnaire were distributed among them to respond. The reliability of the Questionnaire was evaluated by Cronbach’s α, retest, and split-half coefficient, and then the criterion validity with other questionnaires was evaluated to determine the psychometric properties of the ANPS. The factor structure was assessed via confirmatory factor analysis. Results : The results of the factor analysis indicated that ANPS has six factors, and checking the reliability by using Cronbach’s α, retest and split-half coefficient reflects the stability of the scale and the criterion validity of the ANPS with other questionnaires showed desirable discriminant and convergent validity. Conclusions : Overall, the findings indicated that ANPS has good psychometric properties in normal samples, and the scale can be used in studies in normal samples.